'n Kritiese evaluering van die kompromie as etiese figuur in die teologiese etiek van J. Douma, J.A. Heyns, S.J. Ridderbos en W.H. Velema - L. O. K. Lategan (Acta Theologica)
Although the concept of a compromise is known in ethics, very little attention has been paid to the meaning of this concept in Reformed Ethics. In this article the author looks into the meaning of the compromise in the theological-ethical frameworks of J. Douma, J.A. Heyns, S.J. Ridderbos and W.H. Velema. In analysing this concept, it is pointed out that a compromise has to do with the choice between two conflicting norms in a borderline situation. In a borderline situation these norms are in conflict with each other and a conflict of interest is created. It then necessitates a choice between one of the norms in a borderline situation. To this choice is then referred to as a choice between the lesser of two evils. This is where the compromise comes into play.